Sodium positive electrode material, sodium positive electrode plate and battery

By introducing doped metal ions into the O3 type sodium positive electrode material and adopting high shear co-precipitation technology, the problem of low circulation retention of the positive electrode material of sodium ion battery is solved, and the stability of Na+ transfer rate and electrochemical performance is improved.

CN119208589APending Publication Date: 2024-12-27TIANJIN UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411356663.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-27
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

During the charging and discharging process, the positive electrode material of sodium ion battery has problems such as low cycling retention rate, interlayer slippage and electron transmission, resulting in unstable electrochemical performance.

Method used

An appropriate proportion of doped metal ions are introduced into the O3-type sodium positive electrode material, and co-precipitation is carried out by high shearing method to form a uniformly dispersed doped structure, expand the sodium layer spacing, and improve the Na+ transfer rate and cycle retention rate.

Benefits of technology

The cycle retention and rate performance of the positive electrode material of sodium ion battery is improved, and the stability and efficiency of electrochemical performance are enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119208589A_ABST
    Figure CN119208589A_ABST
Patent Text Reader

Abstract

The invention discloses a sodium positive electrode material, the sodium positive electrode material is of an O3 type, the chemical general formula is NaNixMn0. 5A0. 5xO2, x is more than or equal to 0.49 and less than 0.5, and A is selected from one or more of In, Sm, La and Ti. According to the scheme, a certain proportion of metal elements with relatively large ion radiuses are doped on the basis of an O3 type sodium positive electrode material, so that the interlayer spacing is enlarged, and the transmission rate and efficiency of Na < + > ions are improved; meanwhile, doped metal ions with a proper proportion are introduced into a crystal structure of the O3 type sodium positive electrode material, so that the cycle retention rate of the sodium ion battery positive electrode material can be effectively improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of sodium ion batteries, and more specifically, relates to a heteroatom-doped nickel-manganese-based sodium positive electrode material, a sodium positive electrode sheet and a battery. Background Art

[0002] As an emerging energy storage technology, sodium-ion battery technology has developed rapidly in recent years. Compared with lithium-ion batteries, sodium-ion batteries have advantages in the abundance and cost of main raw materials. Sodium is the sixth largest element in the earth's crust, with extensive reserves worldwide and relatively low prices, which makes sodium-ion battery technology more sustainable and economical. Among various sodium-ion battery positive electrode materials, layered metal oxide positive electrode materials have become the research focus in the field of positive electrode materials due to their advantages such as high capacity and low cost. In recent years, literature has reported that doping transition metal ions such as Mn, Fe, Cu, Ni, Co, Cr, Ir, Ru, etc. inside the layered positive electrode materials of sodium-ion batteries can change their crystal structure and thus improve their electrochemical performance (Sun Yuanyuan, Li Siqing, Wang Chengru, etc. Research progress of layered transition metal oxide positive electrode materials for sodium-ion batteries [J]. Rare Metals, 2022, 46(06): 776-795.). However, due to the limited interlayer spacing of sodium-ion battery positive electrode materials, Na + (0.102nm) transmission is subject to certain restrictions; sodium layered cathode materials are mainly divided into two structures, O3 and P2. O3 type materials undergo a series of phase changes such as O3→O′3→P3→O3′ during the charge and discharge process. The volume change causes particle cracking and pulverization, and the electron transport is affected and the electrochemical performance is reduced; the problems existing in the application of sodium ion battery cathode materials include: complex phase changes during the charge and discharge process lead to interlayer slippage, resulting in significant changes in interlayer spacing and volume; serious interface side reactions between electrodes and electrolytes; the presence of Na + / vacancy ordering phenomenon, etc. These problems make it difficult for its electrochemical performance to meet the needs of practical application scenarios (Zuo Wenhua, Yang Yong, Synthesis, Structure, Electrochemical Mechanisms, and Atmospheric Stability of Mn-Based Layered Oxide Cathodes for Sodium Ion Batteries, Accounts of Materials Research, 2022, 3(7): 709-720.).

[0003] The prior art of Chinese patent application publication number CN114784266A discloses a new type of nickel-manganese-based hierarchical sodium-ion battery positive electrode material. The prior art successfully induces Na+ by doping one or more metal ions in the TM layer of the nickel-manganese-based hierarchical positive electrode oxide and regulating the occupancy of two different Wyckoff sites. + The Nae / Naf ratio was adjusted by rearrangement, and a Ni / Mn-based cathode material with increased Na content and enhanced Nae / Naf ratio was prepared. + However, in this scheme, without Li + In the system, the performance improvement is not significant. For example, in Example 1, the prepared nickel-manganese-based layered oxide positive electrode material has the general formula of Na 7 / 9 Ni 1 / 3 Mn 5 / 9 Ti 1 / 9 For O2, although its charge and discharge capacity value in the first cycle is at a relatively high level, its charge and discharge capacity drops significantly after about 25 cycles.

[0004] Therefore, there is an urgent need to develop a sodium ion battery positive electrode material that can simultaneously meet the requirements of high transmission performance and cycle retention rate. Summary of the invention

[0005] 1. Problem to be solved

[0006] The first purpose of the present invention is to address the problem of low cycle retention rate of sodium ion battery positive electrode materials. By introducing an appropriate proportion of doped metal ions into the lattice structure of O3 type sodium positive electrode materials, a doped and modified O3 type layered sodium positive electrode material is provided, which improves the sodium ion transmission rate while keeping the cycle retention rate of the sodium ion battery positive electrode material at a higher level.

[0007] The second purpose of the present invention is to solve the problem of uneven doping of sodium positive electrode materials obtained by existing doping methods, and adopt a high shear method for co-precipitation to make the doped metal ions enter the lattice structure to obtain a sodium positive electrode material in which the doped metal ions are uniformly dispersed. When the sodium positive electrode material is used in a battery, the battery specific capacity, cycle stability and rate performance are comprehensively improved.

[0008] Based on the first and second purposes of the present invention, the present invention provides a sodium positive electrode sheet and a battery with improved cycle performance.

[0009] 2. Technical solution

[0010] In order to solve the above problems, the technical solution adopted by the present invention is as follows:

[0011]

Sodium cathode materials

[0012] The first aspect of the present invention provides a sodium cathode material, which is of the O3 type and has a chemical general formula of NaNi x Mn 0.5 A 0.5-x O2, where 0.45 ≤ x < 0.5, and A is selected from one or more of In, Sm, La, and Ti.

[0013] It should be noted that in the cathode material of a sodium-ion battery, the two-dimensional layered structure Na x MO2 is divided into the O type (x ≈ 1, O2 and O3, presenting a NaO6 octahedron) and the P type (0.6 < x < 0.8, P2 and P3, presenting a NaO6 triangular prism) according to the Na atom occupancy. Due to the relatively large radius of Na + , the cathode material is prone to multiple phase transitions and poor reversibility during charge and discharge, resulting in poor mass transfer inside the particles, crack generation, and reduced cycle retention rate. The sodium cathode material of the present invention is doped with a metal A with a relatively large ionic radius on the basis of the O3-type sodium cathode material, which can adjust the lattice constant of the sodium cathode material, expand the layer spacing of the sodium cathode material, and improve the reversibility of the material structure phase transition during charge and discharge, thereby improving the transmission rate and efficiency of Na + ions, and thus improving its electrochemical performance. At the same time, it is found in the present invention that the doping amount of the metal A with a relatively large radius should not be too high, for example, it should not be higher than 0.05 (taking the Na ion content as 1). When the doping amount of the metal A with a relatively large radius is high, a reduction in the cycle retention rate is shown in the O3-type sodium cathode material.

[0014] As a preference for any implementation manner of the first aspect of the present invention, the chemical general formula of the sodium cathode material is NaNi x Mn 0.5 In 0.5-x O2, NaNi x Mn 0.5 Sm 0.5-x O2, NaNi x Mn 0.5 La 0.5-x O2, NaNi x Mn 0.5 Ti 0.5-x O2. Considering that the synergistic effect of dual-metal doping is not entirely beneficial, and at the same time, single-metal doping usually involves lower material and processing costs and is prone to form a uniform and stable structure in the crystal structure, which is more conducive to performance improvement. Therefore, single-metal doping is preferably carried out in the present invention.

[0015] As a preferred embodiment of any embodiment of the first aspect of the present invention, 0.492≤x<0.5, preferably 0.495≤x<0.5, and more preferably, 0.495≤x≤0.499. It is found in the present invention that when the doping amount of metal A gradually increases (with the Na ion content as 1), the O3 type sodium positive electrode material of the present invention exhibits gradually improved charge and discharge capacity and cycle retention rate, but when the doping amount of metal A exceeds 0.003, the cycle retention rate of the O3 type sodium positive electrode material of the present invention shows a downward trend. Therefore, under the system of the present invention, it is preferred that the doping amount of metal A does not exceed a specific range of 0.005.

[0016] As a preferred embodiment of any one of the first aspects of the present invention, the sodium interlayer spacing in the sodium positive electrode material is not less than The sodium interlayer spacing in the sodium positive electrode material described above is calculated based on the XRD data of the sodium positive electrode material, and the calculation method of the transition metal layer and the sodium layer spacing is:

[0017] T (TMO6) =(2 / 3-2Z ox )c

[0018] T (NaO6) =(c / 3-T (TMO6) )

[0019] Among them, a and c represent the two sets of edge lengths of the unit cell (i.e. the axis length of the crystal), and the unit is Vol represents the volume of the unit cell, in units of Zox is the z-axis coordinate of oxygen in the lattice; T TMO6 is the transition metal interlayer spacing, in units of T NaO6 is the sodium interlayer spacing, in

[0020] It is worth noting that the sodium interlayer spacing in the sodium positive electrode material of the present invention is larger than that of the sodium positive electrode material without A metal doping. The increase in the sodium interlayer spacing after doping is beneficial to the Na + The transmission rate and efficiency are improved.

[0021] As a preferred embodiment of any embodiment of the first aspect of the present invention, the sodium positive electrode material synthesized by the high shear method has a good sphericity of particles and a particle size of no more than 5 μm, which is much smaller than the particle size of ordinary stirred synthetic materials.

[0022] It should be noted here that for sodium positive electrode materials, small particle size can shorten the transmission path of sodium ions. At the same time, at a smaller particle size, the active sites of the electrode material are more easily wetted by the electrolyte, which is conducive to the embedding and extraction of sodium ions, thereby improving the charge and discharge capacity and cycle stability of the battery.

[0023]

Preparation method of sodium positive electrode material

[0024] A second aspect of the present invention provides a method for preparing a sodium positive electrode material, comprising a precursor preparation step, wherein the precursor preparation step comprises:

[0025] Providing a first solution containing a manganese source, a nickel source and an A source; wherein the A is selected from one or more of samarium, lanthanum, titanium or indium;

[0026] Providing a second solution containing a precipitant; wherein the precipitant is used to precipitate manganese, nickel and A;

[0027] Contacting, mixing and reacting the first solution and the second solution to obtain a precursor;

[0028] The stoichiometric ratio of the manganese source, the nickel source and the A source is 0.5:x:(0.5-x), wherein 0.49≤x<0.5. Preferably, 0.492≤x<0.5, and more preferably, 0.495≤x<0.5.

[0029] Under the above-mentioned metal source raw material ratio and precursor preparation steps, and then sequentially undergoing the sodiumization step and the roasting step, an O3 type sodium positive electrode material with excellent cycle performance can be obtained.

[0030] As a preferred embodiment of any one of the second aspects of the present invention, the sodium positive electrode material obtained by the preparation method is an O3 type sodium positive electrode material, and the chemical formula is NaNi x Mn 0.5 A 0.5-x O2, wherein 0.49≤x<0.5, and A is selected from one or more of In, Sm, La, and Ti.

[0031] As a preferred embodiment of any one of the second aspects of the present invention, in the sodium positive electrode material, 0.492≤x<0.5.

[0032] As a preferred embodiment of any one of the second aspects of the present invention, in the sodium positive electrode material, 0.495≤x<0.5. More preferably, in the sodium positive electrode material, 0.495≤x≤0.499.

[0033] As a preference of any embodiment of the second aspect of the present invention, the process of contacting, mixing and reacting the first solution and the second solution is carried out under high shear conditions.

[0034] As described herein, the first solution and the second solution are contacted and mixed under high shear conditions, which can avoid the situation in which the doping atoms are unevenly distributed in the layered material due to the difference of several orders of magnitude in the solubility product constant of the precipitate when the doping atoms are introduced by the traditional method. In addition, when the process is carried out under high shear conditions, the particle size of the sodium positive electrode material obtained is uniform and less than 5 μm.

[0035] As a preferred embodiment of any embodiment of the second aspect of the present invention, the shearing speed of the high shearing condition is not less than 5000 rpm, for example, 6000 rpm, 7000 rpm, 8000 rpm, 9000 rpm, 10000 rpm, 11000 rpm, 12000 rpm, 15000 rpm.

[0036] Under this condition, due to the good micro-mixing performance of the high shear mixer, the supersaturation can be effectively adjusted during the reaction, so that the doping atoms are evenly distributed in the material.

[0037] As a preferred embodiment of any embodiment of the second aspect of the present invention, the shear rate of the high shear condition is not higher than 12000 rpm.

[0038] Theoretically, although the faster the high shear speed, the better the micro-mixing effect, it also brings higher energy consumption, so the high shear speed should be limited to an appropriate range.

[0039] As a preference of any embodiment of the second aspect of the present invention, the reaction temperature under the high shear conditions is not less than 30°C.

[0040] As a preference of any embodiment of the second aspect of the present invention, the reaction temperature under the high shear condition is not higher than 80°C.

[0041] As a preference of any embodiment of the second aspect of the present invention, the reaction temperature under the high shear condition is 40-60°C.

[0042] As a preferred embodiment of any embodiment of the second aspect of the present invention, the mixing rate under the high shear condition does not exceed 2.5 mL / min.

[0043] It should be noted that the mixing rate herein is defined as the total volume of the first solution and the second solution mixed per minute.

[0044] As a preferred embodiment of any one of the second aspects of the present invention, the concentration of total metal ions in the first solution is between 1.0 and 2.5 mol / L.

[0045] As a preferred embodiment of any one of the second aspects of the present invention, the precipitant in the second solution is sodium carbonate, wherein the concentration of sodium ions is between 1.0 and 2.5 mol / L.

[0046] It should be noted here that, from the perspective of uniformity of solution mixing, the concentrations of the first solution and the second solution should not be too high, and low concentrations are more conducive to uniform mixing at each moment; but from the perspective of reaction rate, too low concentrations of the first solution and the second solution will lead to a decrease in reaction rate. Therefore, in the present invention, the first solution and the second solution preferably have concentrations within the above range.

[0047] As a preferred embodiment of any one of the second aspects of the present invention, the total metal ions in the first solution and the carbonate ions in the second solution are in an equistoichiometric ratio.

[0048] As a preferred embodiment of any embodiment of the second aspect of the present invention, the high shear condition is carried out under the protection of an inert gas. Preferably, the inert gas is selected from nitrogen, argon or helium.

[0049] As a preferred embodiment of any embodiment of the second aspect of the present invention, under the high shear conditions, after the reaction, the slurry is aged, allowed to stand, filtered, and dried to obtain a precursor.

[0050] As a preferred embodiment of any embodiment of the second aspect of the present invention, the aging is to stir the slurry at a low speed, the low speed is not higher than 500 rpm, and the aging time is 1 to 3 hours.

[0051] As a preferred embodiment of any embodiment of the second aspect of the present invention, the standing is placing at room temperature for 10 to 15 hours.

[0052] As a preferred embodiment of any one of the second aspects of the present invention, the method for preparing the sodium positive electrode material further includes a sodiumization step and a calcination step.

[0053] As a preferred embodiment of any embodiment of the second aspect of the present invention, the sodiumization step includes a step of wet grinding the precursor and the sodium source. The molar ratio of the total metal ions in the precursor to the sodium ions in the sodium source is 1:(1.03-1.05).

[0054] As a preferred embodiment of any one of the second aspects of the present invention, the calcination step comprises: subjecting the mixture obtained after the sodiumization step to a first stage calcination and a second stage calcination;

[0055] The temperature of the first stage calcination is 300-600°C and the calcination time is 3-10h;

[0056] The second stage calcination temperature is 700-1000° C., and the calcination time is 15-25 hours.

[0057] As a preferred embodiment of any embodiment of the second aspect of the present invention, the manganese source is selected from one of manganese sulfate, manganese nitrate, manganese oxalate, manganese carbonate or a hydrate thereof.

[0058] As a preferred embodiment of any embodiment of the second aspect of the present invention, the nickel source is selected from one of nickel sulfate, nickel nitrate, nickel oxalate, nickel carbonate or a hydrate thereof.

[0059] As a preference of any embodiment of the second aspect of the present invention, the source A is an indium source selected from indium nitrate, indium sulfate, indium chloride or a hydrate thereof.

[0060] As a preferred embodiment of any embodiment of the second aspect of the present invention, the source A is a samarium source, selected from samarium nitrate, samarium chloride, samarium oxalate or a hydrate thereof.

[0061] As a preferred embodiment of any embodiment of the second aspect of the present invention, the source A is a lanthanum source selected from lanthanum nitrate, lanthanum sulfate, lanthanum chloride or a hydrate thereof.

[0062] As a preferred embodiment of any embodiment of the second aspect of the present invention, the source A is a titanium source selected from one of titanium nitrate, titanium tetrachloride, titanium oxysulfide or a hydrate thereof.

[0063] As a preferred embodiment of any embodiment of the second aspect of the present invention, the sodium source in the sodiumization step is selected from sodium oxides, alkalis or salts. Preferably, it is at least one of sodium carbonate, sodium nitrate, sodium bicarbonate, sodium acetate, sodium hydroxide, sodium oxide and sodium peroxide; more preferably, it is at least one of sodium carbonate, sodium bicarbonate, sodium hydroxide and sodium acetate; most preferably, it is at least one of sodium carbonate and sodium acetate.

[0064]

Sodium cathode sheet

[0065] The third aspect of the present invention provides a sodium positive electrode sheet, which comprises the sodium positive electrode material described in any embodiment of the first aspect of the present invention, or comprises the sodium positive electrode material prepared by the method of any embodiment of the second aspect of the present invention.

[0066] As a preferred embodiment of any one of the third aspects of the present invention, the sodium positive electrode sheet further includes a conductive agent and a binder.

[0067] As a preferred embodiment of any embodiment of the third aspect of the present invention, the conductive agent is selected from at least one of conductive carbon black (Super P), graphene, single-walled carbon nanotubes, multi-walled carbon nanotubes and carbon fibers.

[0068] As a preferred embodiment of any embodiment of the third aspect of the present invention, the binder is selected from at least one of polyvinylidene fluoride (PVDF), styrene-butadiene rubber, polyvinyl alcohol, polytetrafluoroethylene, polyethylene, polypropylene, polyacrylic acid, sodium carboxymethyl cellulose and carboxymethyl cellulose.

[0069]

Battery

[0070] The fourth aspect of the present invention provides a battery, comprising the sodium positive electrode material described in any embodiment of the first aspect of the present invention, or the sodium positive electrode material prepared by the preparation method described in any embodiment of the second aspect of the present invention, or the sodium positive electrode sheet described in any embodiment of the third aspect of the present invention.

[0071] As a preferred embodiment of any one of the fourth aspects of the present invention, the battery further includes a negative electrode sheet, a separator and an electrolyte.

[0072] As a preferred embodiment of any one of the fourth aspects of the present invention, the negative electrode sheet may include a sodium negative electrode sheet conventionally used in the art.

[0073] As a preferred embodiment of any one of the fourth aspects of the present invention, the diaphragm may include a diaphragm commonly used in the art, for example, at least one of GF / A, GF / B, GF / C, GF / D and a nanofiber membrane.

[0074] As a preferred embodiment of any embodiment of the fourth aspect of the present invention, the electrolyte is selected from at least one of sodium perchlorate and sodium hexafluorophosphate.

[0075] As a preferred embodiment of any embodiment of the fourth aspect of the present invention, the battery has a cycle retention rate of not less than 55%, preferably not less than 60%, after 100 cycles in a voltage range of 2.0 to 4.0 V, a constant current density of 1C of 170 mAh / g, and 25°C.

[0076] 3. Beneficial effects

[0077] Compared with the prior art, the sodium positive electrode material provided by the present invention has the following beneficial effects:

[0078] (1) The sodium positive electrode material of the present invention is doped with a certain proportion of A element with a larger ion radius on the basis of O3 type sodium positive electrode material, which is beneficial to the expansion of interlayer spacing and improves the Na + At the same time, an appropriate proportion of doped metal ions are introduced into the crystal structure, which makes the cycle retention rate of the sodium ion battery positive electrode material at a high level.

[0079] (2) The method for preparing the sodium positive electrode material of the present invention preferably adopts a high shear method, and utilizes high shear force to introduce the doped metal ions (A) into the crystal structure of the O3 type sodium positive electrode material. The doped metal ions with larger ionic radius in the crystal structure can provide support and form a larger interlayer distance. Compared with the O3 type sodium positive electrode material prepared by the ordinary mixing method, the interlayer structure of the O3 type sodium positive electrode material obtained by the high shear method is more uniform, which is further beneficial to the Na + The interlayer transmission rate and efficiency are improved. At the same time, due to the use of high shear force to effectively adjust the dissolution-precipitation equilibrium of different transition metals, a precursor with uniform concentration distribution of each component is formed, making the performance of the prepared sodium positive electrode material more stable. BRIEF DESCRIPTION OF THE DRAWINGS

[0080] Figure 1 The NaNi prepared in Example 1 0.497 Mn 0.5 In 0.003 SEM image of O2 cathode material;

[0081] Figure 2 The NaNi prepared in Example 1 0.497 Mn 0.5 In 0.003 XRD pattern of O2 cathode material;

[0082] Figure 3 The NaNi prepared in Example 5 0.499 Mn 0.5 In 0.001 XRD pattern of O2 cathode material;

[0083] Figure 4 The NaNi prepared in Example 6 0.495 Mn 0.5 In 0.005 XRD pattern of O2 cathode material;

[0084] Figure 5 The NaNi prepared in Example 1 0.5 Mn 0.5 XRD pattern of O2 cathode material;

[0085] Figure 6 The NaNi prepared in Example 1 0.497 Mn 0.5 In 0.003 EDS image of O2 cathode material;

[0086] Figure 7 The NaNi prepared in Example 2 0.497 Mn 0.5 In 0.003 SEM image of O2 cathode material;

[0087] Figure 8 The NaNi prepared in Examples 1, 5, 6 and Comparative Example 1 0.497 Mn 0.5 In 0.003 O2、NaNi 0.499 Mn 0.5 In 0.001 O2、NaNi 0.495 Mn 0.5 In 0.005 O2、NaNi 0.5 Mn 0.5 Cycling performance diagram of O2 cathode material under 1C conditions;

[0088] Fig. 9 It is NaNi obtained in Examples 2, 3, and 4. 0.497 Mn 0.5 Sm 0.003 O2、NaNi 0.499 Mn 0.5 La0.001 O2、NaNi 0.495 Mn 0.5 Ti 0.005 Cycling performance diagram of O2 cathode material under 1C conditions;

[0089] Fig.10 The NaNi prepared in Example 1 0.497 Mn 0.5 In 0.003 O2 and NaNi prepared in Comparative Example 2 0.497 Mn 0.5 In 0.003 Cycling performance diagram of O2-C cathode material under 1C conditions. DETAILED DESCRIPTION

[0090] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which the invention belongs; the term "and / or" used herein includes any and all combinations of one or more of the associated listed items.

[0091] If the specific conditions are not specified in the examples, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. If the manufacturers of the reagents or instruments are not specified, they are all conventional products that can be purchased commercially.

[0092] As used herein, the term "about" is used to provide flexibility and imprecision associated with a given term, measurement or value. The degree of flexibility for a particular variable can be easily determined by one skilled in the art.

[0093] Concentration, amount and other numerical data can be presented in range format herein.It should be understood that such range format is only used for convenience and simplicity, and should be flexibly interpreted as not only including the numerical value clearly described as range limit, but also including all single numerical values ​​or sub-ranges contained in the range, just as each numerical value and sub-range are clearly described.For example, the numerical range of about 1 to about 4.5 should be interpreted as not only including the limit value of 1 to about 4.5 clearly described, but also including single numerals (such as 2,3,4) and sub-ranges (such as 1 to 3,2 to 4, etc.).The same principle is applicable to the scope of only narrating a numerical value, such as "less than about 4.5", which should be interpreted as including all the above-mentioned values ​​and ranges.In addition, no matter how the breadth of the described range or feature is, this explanation should be applicable.

[0094] It should be noted that the numerical expressions such as "first" and "second" in the present invention are only used to distinguish different substances or usages, and do not represent the difference in order.

[0095] Any steps recited in any method claim may be performed in any order and are not limited to the order of appearance in the claims.

[0096] Accordingly, the scope of the present invention should be determined only by the appended claims and their legal equivalents, rather than by the descriptions and examples given herein.

[0097] The positive electrode material of the present invention can be prepared by the following method: a manganese source, a nickel source and an A source are weighed according to a required stoichiometric ratio and then uniformly mixed to obtain a first solution, and a precipitant (such as sodium carbonate) is weighed according to a required stoichiometric ratio (carbonate and total other metal ions are equivalent, so that all metal ions are just precipitated by carbonate) and then uniformly mixed to obtain a second solution. Under the protection of an inert gas, at 30 to 80° C., the first solution and the second solution are respectively transported to a high shear device by a pump, and the first solution and the second solution are slowly contacted and mixed at 8000 to 12000 rpm to cause a coprecipitation reaction, wherein when the mixing rate of the first solution and the second solution does not exceed 2.5 mL / min, the structural stability of the sodium positive electrode material can be further improved, and after the coprecipitation reaction, the precursor is obtained by aging, standing, filtering and drying. The precursor and sodium source are weighed according to the stoichiometric ratio (sodium ion to total other metal ion molar ratio (1.03-1.05):1), and the sodiumization process is carried out by wet grinding with ethanol, followed by calcination under air conditions. The first calcination stage is calcined at 300-600°C for 3-10h; then the temperature is raised to 700-1000°C in the second calcination stage for 15-25h. The heteroatom-doped nickel-manganese-based sodium positive electrode material NaNi is prepared. x Mn 0.5 A 0.5-x O2.

[0098] Among them, the precipitant or sodium source includes at least one of sodium carbonate, sodium bicarbonate, sodium hydroxide, sodium oxide, sodium peroxide, and sodium acetate; the nickel source is selected from one of nickel sulfate, nickel nitrate, nickel oxalate, nickel carbonate and their hydrated compounds; the manganese source is selected from one of manganese sulfate, manganese nitrate, manganese oxalate, manganese carbonate and their hydrated compounds; the A source is selected from at least one of indium nitrate, indium sulfate, indium chloride, samarium nitrate, samarium chloride, samarium oxalate, lanthanum nitrate, lanthanum sulfate, lanthanum chloride, titanium nitrate, titanium tetrachloride, titanium oxysulfide, and their hydrated compounds.

[0099] The doped sodium battery positive electrode material prepared in the embodiment of the present invention has the characteristics of excellent cycle performance, excellent rate performance and good safety performance.

[0100] The present invention is further described below in conjunction with specific embodiments.

[0101] Example 1

[0102] NeNi 0.497 Mn 0.5 In 0.003 Preparation of O2

[0103] Manganese sulfate, nickel sulfate and indium nitrate were mixed according to n(Ni 2+ ):n(Mn 2+ ):n(In 3+ ) The stoichiometric ratio is 0.497:0.5:0.003, and then the mixture is weighed and uniformly mixed in water to prepare a first solution with a total metal ion concentration of 2 mol / L and a solution volume of 100 ml; the precipitant sodium carbonate is weighed and dissolved in water according to the ratio of carbonate to the total metal ion equivalent in the first solution to prepare a second solution, wherein the carbonate concentration is about 2.003 mol / L and the solution volume is 100 ml. The first solution and the second solution are respectively transported to a high shear device by a pump, and under the protection of inert gas and 10000r, the first solution and the second solution are rapidly contacted, mixed and reacted at 55°C, and the mixing rate is about 2mL / min. After the mixing is completed, the high shear reaction is continued for about 5 minutes, and the precursor is obtained after aging at 200rpm for 2 hours, standing for 12 hours, filtering and drying. In the sodiumization stage, the precursor and sodium acetate, a sodium source, were weighed according to the stoichiometric ratio of 1:1.03 (the ratio of the total amount of metal ions in the precursor to the total amount of sodium ions), and wet-milled with ethanol for 30 min; then, the first stage of calcination was carried out at 450 ° C for 6 h; then the second stage of calcination was carried out at 850 ° C for 20 h to prepare the heteroatom-doped nickel-manganese-based sodium ion positive electrode material NaNi 0.497 Mn 0.5 In 0.003 O2.

[0104] Example 2

[0105] NeNi 0.497 Mn 0.5 Sm 0.003 Preparation of O2

[0106] The other steps in this embodiment are the same as those in embodiment 1, except that the In source is replaced by an Sm source. Specifically, the Sm source is samarium nitrate, and NaNi 0.497 Mn 0.5 Sm 0.003 O2.

[0107] Example 3

[0108] NeNi 0.497 Mn 0.5 La 0.003 Preparation of O2

[0109] The other steps in this embodiment are the same as those in embodiment 1, except that the In source is replaced by a La source. Specifically, the La source is lanthanum nitrate, and NaNi 0.497 Mn 0.5 La 0.003 O2.

[0110] Example 4

[0111] NeNi 0.497 Mn 0.5 Ti 0.003 Preparation of O2

[0112] The other steps in this embodiment are the same as those in embodiment 1, except that the In source is replaced by a Ti source. Specifically, the Ti source is titanium oxysulfide, and NaNi 0.497 Mn 0.5 Ti 0.003 O2.

[0113] Example 5

[0114] NeNi 0.499 Mn 0.5 In 0.001 Preparation of O2

[0115] The other steps in this embodiment are the same as those in embodiment 1, except that: manganese sulfate, nickel sulfate and indium nitrate are mixed according to n(Ni 2+ ):n(Mn 2+ ):n(In 3+ ) with a stoichiometric ratio of 0.499:0.5:0.001 and then evenly mixed in water. Finally, NaNi 0.499 Mn 0.5 In 0.001 O2.

[0116] Example 6

[0117] NeNi 0.495 Mn 0.5 In 0.005 Preparation of O2

[0118] The other steps in this embodiment are the same as those in embodiment 1, except that: manganese sulfate, nickel sulfate and indium nitrate are mixed according to n(Ni 2+ ):n(Mn 2+ ):n(In 3+ ) with a stoichiometric ratio of 0.495:0.5:0.005 and then evenly mixed in water. Finally, NaNi 0.495 Mn 0.5 In 0.005 O2.

[0119] Comparative Example 1

[0120] NeNi 0.5 Mn 0.5 Preparation of O2

[0121] The other steps in this comparative example are the same as those in Example 1, except that: no In source is added, n(Ni 2+ ):n(Mn 2+ )The stoichiometric ratio is 0.5:0.5. Finally, NaNi 0.5 Mn 0.5 O2.

[0122] Comparative Example 2

[0123] The other steps in this comparative example are the same as those in Example 1, except that:

[0124] The reaction process does not use a high shear step, but a conventional ordinary stirring method. The specific method is to pump the first solution and the second solution into an ordinary stirring device respectively, and slowly contact and mix the first solution and the second solution at 1000 rpm to cause a coprecipitation reaction. Finally, NaNi 0.497 Mn 0.5 In 0.003 O2-C.

[0125] Example 7

[0126] Preparation of batteries

[0127] (1) Preparation of positive electrode

[0128] The positive electrode material, conductive carbon black and polyvinylidene fluoride obtained in the embodiment and comparative example were respectively added with a mass ratio of 80:10:10, and mixed with an appropriate amount of N-methylpyrrolidone (NMP) for 1 hour to prepare a uniform slurry, and the positive electrode sheet was obtained by coating, rolling and drying, and finally cut into a circular electrode sheet with a diameter of 1 cm. The sheet was transferred to a glove box with a water content and an oxygen content of less than 0.1 ppm.

[0129] (2) Preparation of batteries

[0130] In a glove box, the positive electrode sheet (10 mm) was assembled with the positive and negative electrode shells, springs, gaskets, diaphragms (nanofiber membranes, purchased from Jiaxing Naxin New Materials Technology Co., Ltd.), electrolyte (1M NaClO4 in PC = 100 Vol% with 5% FEC) and sodium sheet negative electrode (15.6 mm, purchased from Jiaxing Naxin New Materials Technology Co., Ltd.) into a CR2032 button cell. The assembled battery was placed in a 25°C constant temperature box. After standing for 6 hours, the battery was first activated at a constant current density of 0.1C, 0.2C, and 0.5C (1C = 170 mAh / g) in the voltage range of 2.0 to 4.0V, and then the charge and discharge cycle test was performed at a constant current density of 1C.

[0131] Test Case I

[0132] (1) SEM

[0133] The SEM images of the sodium positive electrode materials in Example 1 and Comparative Example 2 are as follows: Figure 1 and Figure 7 As shown, the primary particles of the sodium positive electrode material synthesized by high shear in Example 1 are relatively small, all below 5 μm, and have good sphericity. The reduction in particle size is beneficial to increasing the contact area with the electrolyte and thus improving the electrochemical performance.

[0134] (2) XRD test

[0135] The positive electrode materials prepared in the examples and comparative examples were subjected to XRD test.

[0136] like Figure 2 , 3 As shown in , 4, and 5, the materials obtained in Examples 1, 5, 6, and Comparative Example 1 are all O3-type sodium positive electrode materials, and the materials show a diffraction pattern similar to the α-NaFeO2 structure of the R3m space group, which is similar to NaNi 0.5 Mn 0.5 Compared with the standard PDF card (54-0887) of O2, each peak type has a high degree of overlap, and the unit cell parameter c / a is greater than 4.9, indicating that the modified samples all maintain a highly ordered layered structure and good crystallinity. The XRD data of Examples 1-6 and Comparative Example 1 were Rietveld refined using GSAS II software to study the changes in the lattice parameters of the materials. The results and analysis are shown in Table 1.

[0137] Table 1 Lattice parameters obtained by refining XRD data of Examples 1-6 and Comparative Example 1

[0138]

[0139] Note: a, b, c represent the three sets of edge lengths in the X, Y, and Z directions of the unit cell (i.e., the axis length of the crystal), where a = b; Vol represents the volume of the unit cell, Zox is the z-axis coordinate of oxygen in the lattice, T TMO6 is the transition metal interlayer spacing; T NaO6 is the sodium interlayer spacing.

[0140] Compared with the sample NaNi in Comparative Example 1 0.5 Mn 0.5 Compared with O2, the interlayer spacing of the sodium layer (T NaO6 ) have increased, which is more conducive to Na + The diffusion of different contents of In in Examples 1, 5 and 6 3+ Doping data comparison, with In 3+ As the content increases, the a-axis expands and the c-axis shrinks. The spacing between the transition metal layer and the sodium layer is calculated by the following method:

[0141] T (TMO6) =(2 / 3-2Z ox )c

[0142] T (NaO6) =(c / 3-T (TMO6) )

[0143] It can be seen that when the doping amount is 0.3% (i.e. x = 0.497), the material has a larger sodium interlayer spacing, which is more conducive to Na + The ion transfer rate and efficiency are improved, thereby improving its electrochemical performance.

[0144] (3) EDS

[0145] The EDS of the sodium cathode material of Example 1 is as follows Figure 6 As shown, each element is evenly distributed on the surface of the material.

[0146] (4) EIS test

[0147] The sodium positive electrode materials prepared in Examples 1, 5, 6 and Comparative Example 1 were subjected to EIS test.

[0148] The electrochemical impedance of the material was tested when it was charged to 4.0V in the first cycle and the 100th cycle at a constant current density of 1C = 170mAh / g, where R 总 Including R s (Ohm resistance) R f (surface film resistance), R ct (charge transfer impedance), the results are shown in Table 2. Compared with the sample NaNi 0.5 Mn 0.5Compared with O2, the In-doped sample has lower impedance during the cyclic charge and discharge process. After 100 cycles, with the increase of In content, the impedance value shows a trend of first decreasing and then increasing, among which the sample in Example 1 has the lowest impedance value, thus having better electrochemical performance.

[0149] Table 2 EIS data of Examples 1, 5, 6 and Comparative Example 1

[0150]

[0151]

[0152] Test Case II

[0153] Half-cell test

[0154] The battery cycle performance of the sodium cathode materials synthesized in Examples 1-6 and Comparative Examples 1-2 is shown in Table 3 and Figure 8-10 shown.

[0155] Table 3 Battery cycle performance of sodium cathode materials synthesized in Examples 1-6 and Comparative Examples 1-2

[0156] Example sample 1C first round 1C100 laps Cycle retention rate Example 1 <![CDATA[NaNi 0.497 Mn 0.5 In 0.003 O2]]> 121.3 74.6 61.5% Example 2 <![CDATA[NaNi 0.497 Mn 0.5 Sm 0.003 O2]]> 105.8 67.8 64.1% Example 3 <h2 style=";text-align:left;direction:ltr"><![CDATA[NaNi <h2 style=";text-align:left;direction:ltr"> 0.497 <h2 style=";text-align:left;direction:ltr"> Mn<h2 style=";text-align:left;direction:ltr"> 0.5 <h2 style=";text-align:left;direction:ltr"> No<h2 style=";text-align:left;direction:ltr"> 0.003 <h2 style=";text-align:left;direction:ltr"> O2]]><h2 style=";text-align:left;direction:ltr"> 101.0 66.4 65.7% Example 4 <![CDATA[NaNi 0.497 Mn 0.5 You 0.003 O2]]> 128.5 82.5 64.2 Example 5 <![CDATA[NaNi 0.499 Mn 0.5 In 0.001 O2]]> 122.9 70.2 57.1% Example 6 <![CDATA[NaNi 0.495 Mn 0.5 In 0.005 O2]]> 120.2 73.1 60.8% Comparative Example 1 <h2 style=";text-align:left;direction:ltr"><![CDATA[NaNi <h2 style=";text-align:left;direction:ltr"> 0.5 <h2 style=";text-align:left;direction:ltr"> Mn<h2 style=";text-align:left;direction:ltr"> 0.5 <h2 style=";text-align:left;direction:ltr"> O2]]><h2 style=";text-align:left;direction:ltr"> 118.5 53.4 45.1% Comparative Example 2 <![CDATA[NaNi 0.497 Mn 0.5 In 0.003 O2-C]]> 105.0 63.1 60.1%

[0157] From the comparison of Comparative Example 1, Example 6, Example 1 and Example 5, it can be seen that Figure 8 , along with NaNi x Mn 0.5 A 0.5-x As the x value in O2 decreases, that is, the amount of In doping increases, until x = 0.497, the battery cycle retention rate shows an upward trend, which indicates that the doping of large-sized A metal ions is conducive to the improvement of the cycle retention rate. However, when x continues to decrease to 0.495, the cycle retention rate decreases. Therefore, under the system of the present invention, the proportion of doped A metal should not be too high. By comparing Comparative Example 1 and Examples 1-4, it can be seen that Figure 8 and Fig. 9 , relative to the undoped O3 type sodium cathode material, A is selected from In, Sm, La, Ti doped NaNi x Mn 0.5 A 0.5-x The O2 material circulation retention rate has been significantly improved.

[0158] By comparing Comparative Example 2 with Example 1, it can be seen that Fig.10 Compared with the sodium cathode material prepared by ordinary stirring rate, the sodium cathode material prepared by high shear mixing has higher discharge capacity both in the first cycle and after 100 cycles under 1C conditions.

[0159] The above content is a schematic description of the present invention and its implementation methods, which is not restrictive. What is shown in the embodiment is only one of the implementation methods of the present invention, and the actual implementation method is not limited thereto. Therefore, if a person of ordinary skill in the art is inspired by it and designs implementation methods and embodiments similar to the technical solution without creative design without departing from the purpose of the invention, they should all fall within the scope of protection of the present invention.

Claims

1. A sodium positive electrode material, characterized in that The sodium positive electrode material is of O3 type, and its general chemical formula is NaNi x Mn 0.5 A 0.5- x O2, wherein 0.49≤x<0.5, A is selected from one or more of samarium, lanthanum, titanium or indium.

2. The sodium positive electrode material according to claim 1, characterized in that 0.495≤x<0.5。 3. The sodium positive electrode material according to claim 1, characterized in that The sodium positive electrode material has a sodium interlayer spacing of not less than 4. A method for preparing a sodium positive electrode material, characterized in that: The method comprises a precursor preparation step, wherein the precursor preparation step comprises: Providing a first solution containing a manganese source, a nickel source and an A source; wherein the A is selected from one of samarium, lanthanum, titanium or indium; providing a second solution comprising a precipitant; Contacting, mixing and reacting the first solution and the second solution to obtain a precursor; The stoichiometric ratio of the manganese source, the nickel source and the A source is 0.5:x:(0.5-x), wherein 0.49≤x<0.

5.

5. The preparation method according to claim 4, characterized in that: The process of contacting, mixing and reacting the first solution and the second solution is carried out under high shear conditions, the shear rate under the high shear conditions is not less than 5000 rpm, preferably, the shear rate under the high shear conditions is not higher than 12000 rpm; and / or the mixing rate under the high shear conditions does not exceed 2.5 mL / min.

6. The preparation method according to claim 5, characterized in that: After the precursor preparation step, it also includes a sodiumization step and a calcination step; The sodiumization step includes the step of wet grinding the precursor and the sodium source; The calcination step comprises: subjecting the mixture obtained after the sodiumization step to first-stage calcination and second-stage calcination; The temperature of the first stage calcination is 300-600°C and the calcination time is 3-10h; The second stage calcination temperature is 700-1000° C., and the calcination time is 15-25 hours.

7. The preparation method according to any one of claims 4 to 6, characterized in that: The manganese source is selected from manganese sulfate, manganese nitrate, manganese oxalate, manganese carbonate or its hydrate; the nickel source is selected from nickel sulfate, nickel nitrate, nickel oxalate, nickel carbonate or its hydrate; The source A is an indium source selected from indium nitrate, indium sulfate, indium chloride or a hydrate thereof; or The source A is a samarium source selected from samarium nitrate, samarium chloride, samarium oxalate or a hydrate thereof; or The source A is a lanthanum source selected from lanthanum nitrate, lanthanum sulfate, lanthanum chloride or a hydrate thereof; or The source A is a titanium source selected from titanium nitrate, titanium tetrachloride, titanium oxysulfide or a hydrate thereof.

8. A sodium positive electrode sheet, comprising the sodium positive electrode material according to any one of claims 1 to 3, or comprising the sodium positive electrode material prepared by the preparation method according to any one of claims 4 to 7.

9. A battery, comprising the sodium positive electrode material according to any one of claims 1 to 3 or the sodium positive electrode material prepared by the preparation method according to any one of claims 4 to 7, or the sodium positive electrode sheet according to claim 8.

10. The battery according to claim 9, characterized in that The battery has a cycle retention rate of not less than 55%, preferably not less than 60%, after 100 cycles at a voltage range of 2.0 to 4.0 V, a constant current density of 170 mAh / g at 1C, and 25° C.